The impact of preconception counselling on pregnancy outcomes and maternal health - Baoum, Shada Omar; Alaklabi, Nouf Mohammed; Ayoub, Yazan Adnan; Alresheedi, Hend Ali; Alalshaikh, Zahra Ahmed; Alshahrani, Nada Mohammed; Alotibi, Aljohraha Mohammed; Albahrani, Kumail Abdulmonem; Alghanim, Manar Ali; Almutairi, Jawaher Fahad; Almagati, Hanan Thenayan (International Journal Of Community Medicine And Public Health, 2023)
Reproductive health is a global concern, characterized by high rates of maternal and infant mortality. Preconception counseling is a comprehensive approach aimed at improving pregnancy outcomes and maternal health. It involves addressing pre-existing medical conditions, promoting lifestyle modifications, and providing education and support to women before conception or during the interconception period. Tailoring counseling to individual needs and risk factors is crucial for optimal outcomes. Although further research is needed to assess the sustained effects of behavioral changes and overall impact, preconception counseling holds significant potential in promoting healthier pregnancies and improving the well-being of women, infants, and families. By prioritizing research in this field, we can better understand and utilize the benefits of preconception counseling, ultimately contributing to the global enhancement of reproductive health. While the impact of preconception counseling on long-term outcomes requires further research, its potential in promoting healthier pregnancies and improving the well-being of women, infants, and families is evident. It has the capacity to address not only the physical aspects of reproductive health but also the emotional, social, and environmental factors that contribute to overall well-being.